Challenges and Management of Acute Coronary Syndrome in Cancer Patients - Costa, Isabela Bispo Santos da Silva; Andrade, Fernanda Thereza de Almeida; Carter, Diego; Seleme, Vinicius B.; Costa, Maycon Santos; Campos, Carlos M.; Hajjar, Ludhmila Abrahão (Frontiers in Cardiovascular Medicine, 2021)
Cancer and Cardiovascular disease are the leading mortality cause in the world. The prevalence of cardiovascular risk factors and coronary artery disease in cancer patients is elevated and it is associated with high mortality. Several mechanisms may contribute for these scenarios such as the proinflammatory and procoagulant states present in cancer patients. The oncological therapy can predispose to acute thrombosis, accelerated atherosclerosis and coronary spasm. The treatment decision must be individualized and based on the cancer history and balancing the bleeding and thrombosis risks.